La convergencia entre el derecho de la competencia y los derechos de propiedad intelectual - Tassano Velaochaga, Hebert Eduardo (2015)
Indecopi has within its functions the defense of free competition and the protection of intellectual property. This institutional design has the advantage of being able to see more clearly what are the points of convergence between the two subject-matter, harmonize them and achieve the goals they have in common. Within this convergence, there are sensitive issues as the granting of compulsory licenses. In this work, we highlight that compulsory licenses are exceptional measures and, to consider its granting, the State must have a procedure that provides confidence and predictability to citizens and clear definitions of what is meant by public interest, emergency and national security. Finally, it is proposed that the granting of compulsory licenses should be justified by a cost benefit analysis showing that is the best choice.